2015
DOI: 10.1136/bjophthalmol-2014-306338
|View full text |Cite
|
Sign up to set email alerts
|

Progressing geographic atrophy: choroidal thickness and retinal sensitivity identify two clinical phenotypes

Abstract: During follow-up, changes in Se and choroidal thickness differed in patients with GA with or without CNV in the fellow eye. These results identify at least two GA phenotypes, in which the development and progression of GA may be primarily due to different pathophysiologic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
(26 reference statements)
1
5
0
Order By: Relevance
“…The same association was less pronounced in eyes with SDD; but in these SDD-eyes, it vanished upon adjusting for the other independent predictors of GA. While SDD stipulate thinner choroids that cannot prognosticate progression to GA, SDD-free eyes with choroidal thickness that is age-appropriate may be protected against new-onset GA. By asserting claims from other studies, 44,45 our findings showed that choroidal thickness and SDD will help distinguish at least two different pathophysiologic mechanisms. Briefly, the findings of this study pointed to structural SDOCT markers that act as independent contributors to the risk of GA, and which may help in deciphering the pathophysiologic mechanisms leading to GA.…”
Section: Discussionsupporting
confidence: 62%
“…The same association was less pronounced in eyes with SDD; but in these SDD-eyes, it vanished upon adjusting for the other independent predictors of GA. While SDD stipulate thinner choroids that cannot prognosticate progression to GA, SDD-free eyes with choroidal thickness that is age-appropriate may be protected against new-onset GA. By asserting claims from other studies, 44,45 our findings showed that choroidal thickness and SDD will help distinguish at least two different pathophysiologic mechanisms. Briefly, the findings of this study pointed to structural SDOCT markers that act as independent contributors to the risk of GA, and which may help in deciphering the pathophysiologic mechanisms leading to GA.…”
Section: Discussionsupporting
confidence: 62%
“…The arithmetic mean of overall retinal threshold is unable to detect subtle functional changes in atrophic macular disease. Several studies have recognized this limitation and investigated the use of additional scotoma-related measures to detect progression, including number and/or proportion of NS, 17 DS, 15 , 16 , 14 17 , and . 13 17 In the light of this, we reported TRV values for each of these measures in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been observed that patients with bilateral GA and those with GA in one eye and CNV in the fellow eye (unilateral GA) differ for both retinal sensitivity and choroidal thickness changes. 69 In patients with unilateral GA, choroid was thinner compared to patients with bilateral GA, and became thinner during follow-up. Otherwise, patients with bilateral GA had a significant reduction in retinal sensitivity from baseline, whereas retinal sensitivity did not significantly change in patients with unilateral GA.…”
Section: Microperimetry In Early Age-related Macular Degenerationmentioning
confidence: 91%
“…On the contrary, photoreceptors are primarily involved in patients with bilateral GA, and the progression of the GA probably depends on their dysfunction, with secondary decrease of visual function. 69…”
Section: Microperimetry In Early Age-related Macular Degenerationmentioning
confidence: 99%